O consumo de benzodiazepÃnicos e antidepressivos por mulheres na EstratÃgia SaÃde da famÃlia. - Bruna Vieira Gomes (2014)
On many occasions, in the face of the suffering and frustrations that life can offer, the most plausible way out seems to be resorting to the use of some kind of psychotropic drug; this led us to question the context of life for users of medications containing benzodiazepine and antidepressive agents. In this study we proposed to analyze the consumption characteristics of medications containing benzodiazepine and/or antidepressive agents by women in the Family Health Strategy from the municipality of Sobral-CearÃ. Seventy-five women participated in this study. This study was completed using the mixed-methods technique at 5 Primary Health Care Centers (PHCC), in the municipality of Sobral and the target public consisted of women - users of medications containing benzodiazepine and/or antidepressive agents for a period greater than 12 consecutive months and accepting participation in this study through signing the Informed Consent Form (ICF). Information was collected by means of a form and a semi-structured interview script, from January to March 2014. Quantitative data were analyzed using descriptive statistics and qualitative data by means of axial coding. The results present the following profile for the women: white/fair skinned (57.3%), married (52.0%), in civil union for over 30 years (36.0%), and literate (76.0%), with family income of one minimal wage or less (74.6%). Concerning the length of use, 66% of the women interviewed had taken medications containing benzodiazepine and/or antidepressive agents for more than 5 years, the longest being 36 years; the main prescriber is the physician at the PHCC. The triggering factors for the consumption of medications containing benzodiazepine and psychotropic drugs were divided into three categories: losses and deaths; relationship problems; health problems. Our findings signaled that the onset of consumption is intimately related to marital and family problems, and the monitoring of these women requires a holistic approach for the medication not to be used as a support, quite often being inadequate for a problem of non-physiological origin. Our study will contribute to the reflection of the users themselves on their relationship with the medication, and for the health team to rethink the care to these women, seeking non-pharmacological strategies to provide the assistance that these women need.